Semantics in business systems : the savvy manager's guide : the discipline underlying web services, business rules, and the Semantic Web - McComb, Dave (Savvy manager's guides., 2004)
Semantics in Business Systems begins with a description of what semantics are and how they affect business systems. It examines four main aspects of the application of semantics to systems, specifically: How do we infer meaning from unstructured information, how do application systems make meaning as they operate, how do practitioners uncover meaning in business settings, and how do we understand and communicate what we have deduced? This book illustrates how this applies to the future of application system development, especially how it informs and affects Web services and business rule- based approaches, and how semantics will play out with XML and the semantic Web. The book also contains a quick reference guide to related terms and technologies. It is part of Morgan Kaufmann's series of Savvy Manager's Guides. * Presents an easy and enjoyable introduction to semantics in the context of business IT systems. * Articulates the business value of semantics, while providing relevant introductory technical background. * Describes the semantic underpinnings of data modeling, business rules, enterprise integration, and Web services. * Contains a handy quick-reference guide to technologies and terminology. * For more information, links, and discussions, go to www.savvymanagers.com.